Enterovirus particles expel capsid pentamers to enable genome release - Buchta, David; Füzik, Tibor; Hrebík, Dominik; Levdansky, Yevgen; Sukeník, Lukáš; Mukhamedova, Liya; Moravcová, Jana; Vácha, Robert; Plevka, Pavel (Nature communications, 2019)
Viruses from the genus Enterovirus are important human pathogens. Receptor binding or exposure to acidic pH in endosomes converts enterovirus particles to an activated state that is required for genome release. However, the mechanism of enterovirus uncoating is not well understood. Here, we use cryo-electron microscopy to visualize virions of human echovirus 18 in the process of genome release. We discover that the exit of the RNA from the particle of echovirus 18 results in a loss of one, two, or three adjacent capsid-protein pentamers. The opening in the capsid, which is more than 120 Å in diameter, enables the release of the genome without the need to unwind its putative double-stranded RNA segments. We also detect capsids lacking pentamers during genome release from echovirus 30. Thus, our findings uncover a mechanism of enterovirus genome release that could become target for antiviral drugs.
Keywords: Chlorocebus aethiops; dvouvláknová RNA; RNA virová; svlékání virového obalu; kapsida; Humans; Enterovirus B, Human; enterovirus B lidský; genom virový; virion; epitelové buňky; lidé; zvířata; Cercopithecus aethiops; simulace molekulární dynamiky; Epithelial Cells; Genome, Viral; Virion; Capsid; Molecular Dynamics Simulation; Hydrogen-Ion Concentration; RNA, Double-Stranded; RNA, Viral; Animals; koncentrace vodíkových iontů; elektronová kryomikroskopie; Virus Uncoating; Cryoelectron Microscopy